George of Bohemia, King of Heretics - Heymann, Frederick Gotthold, 1900- (Princeton legacy library., 1965)
"George of Kunštát and Poděbrady (23 April 1420? 22 March 1471), also known as Poděbrad or Podiebrad (Czech: Jiří z Poděbrad; German: Georg von Podiebrad), was King of Bohemia (1458?1471). He was leader of the Hussites."--Wikipedia.